Democratic Leadership and Employee Performance: Moderating Role of Length of Employment - Koirala, Aarju; Danuwar, Ranjana Kumari; Subedi, Surendra (International Research Journal of MMC, 2024)
Every organization's core is its employees' performance, which is influenced by various elements. Leadership style in particular has a significant impact on employee performance. The purpose of this study is to identify the impact of democratic leadership style on employee performance along with the moderating role of length of employment in this relationship. Through a systematic analysis of existing research, this paper highlights the positive effects of democratic leadership on various aspects of employee performance. It develops a simple regression model, assesses the dummy indicator regression of the variables used, draws upon a comprehensive review of scholarly literature and discusses the results of the analysis which indicate that democratic leadership has a positive and significant impact on employee performance. The emphasis on motivation, communication, and participative behavior that results from managers adopting a democratic leadership style raises employee performance levels. Similarly, length of employment plays significant moderating role in democratic leadership’s impact on employee performance. This paper concludes with a number of theoretical and practical implications, suggestions for managers and policymakers, and lays the groundwork for future academics to conduct a more thorough investigation.